Formation of polyheterocyclic systems by reaction of 2-imino-4-methyl-2H-1-benzopyran-3-carbonitrile with active methylene compounds - DRAPER, SYLVIA MARY (My University, 1996)
2-Imino-4-methyl-2H-1-benzopyran-3-carbonitrile undergoes [1,5] tautomerism in solution to 2-amino-4-methylidene-4H-1-benzopyran-3-carbonitrile. Reaction with one equivalent of compounds containing a reactive methylene group affords simple 4-methylbenzopyran derivatives, and a methylidene derivative (of [1]benzopyrano[2,3-b][1,8]naphthyridine). Reaction with two and three equivalents of malononitrile affords derivatives of [1]benzopyrano[2,3,4-de]quinoline and [1]benzopyrano[2,3,4-de][1,6]-naphthyridine, which had previously been formulated as bicyclic benzopyran derivatives. The X-ray crystal structure of ethyl 3-amino-2-cyano-3-(2-imino-4-methyl-2H-1-benzopyran-3-yl)prop-2-enoate has been determined, showing the presence of two molecules in the asymmetric unit.
PUBLISHED
Keywords: Chemistry